Elevated Plasma Level of Interferon-λ1 in Chronic Spontaneous Urticaria: Upregulated Expression in CD8+ and Epithelial Cells and Induction of Inflammatory Cell Accumulation - S. F. Wang; X. Q. Gao; Y. N. Xu; D. N. Li; H. Y. Wang; S. H. He (Mediators of Inflammation)
Interferon- (IFN-) λ1 is regarded as a potent bio-active molecule in innate immunity. However, little is known about its role in chronic spontaneous urticaria (CSU). We therefore investigated expression of IFN-λ1 in CSU, its cellular location, and its influence on inflammatory cell accumulation by using flow cytometry analysis, skin tissue dispersion, immunohistochemical stain, and a mouse peritoneal inflammation model. The results showed that level of IFN-λ1 was 2.0-fold higher in plasma of the patients with CSU than the level in healthy control (HC) subjects. Among leukocytes examined, only CD8+ T cells expressed more IFN-λ1 in CSU blood. Double labeling immunohistochemical staining revealed that IFN-λ1+ inflammatory cells such as mast cells, eosinophils, B cells, neutrophils, and macrophages were mainly located in dermis, whereas epidermis tissue highly expressed IFN-λ1. IFN-λ1 induced a dose-dependent increase in number of eosinophils, lymphocytes, mast cells, macrophages, and neutrophils in the peritoneum of mice at 6 h following injection, which was inhibited by pretreatment of the animals with anti-intercellular adhesion molecule- (ICAM-) 1 and/or anti-L-selectin antibodies. In conclusion, IFN-λ1 is likely to play a role in the pathogenesis of CSU. Blocking IFN-λ1 production may help to reduce the accumulation of inflammatory cells in the involved CSU skin.